Aspectos fisiológicos da interação entre Physalis peruviana L. e nanotubos de carbono de paredes múltiplas - Corrêa, Patrícia Teixeira (2017)
Carbon nanotubes have many functions, properties and applications that are not found in other materials, making them target of studies. The plant Physalis peruviana L., with elevated germination rate and fast development, was a target for the application of this nanomaterial. In this study, the objective was to investigate the effects of carbon nanotubes over the growth and development of Physalis peruviana L. Initially, micrographs were obtained by means of the transmission electron microscopy with the objective of evaluating the morphological parameters of the carbon nanotubes. In addition, the Raman spectroscopy was used to better understand the chemical composition of the carbon nanotubes. Growth and development analysis were conducted on the plants to evaluate possible interactions between the carbon nanotubes and Physalis peruviana L. This study was conducted using two distinct forms of analysis. The first was conducted with plants developed under in vitro conditions and the second with plants developed under ex vitro conditions. For the in vitro analysis, the effect of the autoclaving process of the cultivation medium containing the carbon nanotubes. For the second treatment of the in vitro analysis, the effect of Physalis peruviana L. seed soaking in solutions containing different concentrations was evaluated. For the ex vitro treatment, the seeds were germinated in plant substrate and the foliar aspersion was done by suspending the carbon nanotubes. The parameters were evaluated in this phase also with the objective of evaluating possible effects of the nanotubes over the plants. The results for both in vitro and ex vitro procedures showed that the carbon nanotubes, in general, presented effects favorable to plant growth and development.